Influence of High-Protein Food on Physical Function of Athletes - Shengze Liu; Nan Wen; HanTao Su (Journal of Food Quality)
In order to explore how high-protein foods can achieve effects on athletes’ bodies, the authors propose a study based on athletes’ physical performance. This method recommends key technical problems and solutions through the information represented by the athlete’s physical function and discovers how high-protein foods enable research into athletic performance. Research has shown that athletes perform high-intensity sports training for a long time, in a state of high-intensity competition, the body’s energy metabolism is strong, and the protein consumption rate is high; protein foods can preserve protein, water, electrolytes, and other nutrientsand supplement about 71% of the body’s nutrition, and it helps to strengthen muscles, relieve sports fatigue, improve immunity, etc., which is of great significance to athletes.